Effect of postural variation on near visual function in myopic subjects - Banik, Ankur; Rashi, G. M.; Sah, Anju Kumari; Ashwini, K. V. (International Journal of Research in Medical Sciences, 2025)
Background: Near visual tasks demand sustained accommodation and convergence, which may vary with body posture. This study examined the effect of sitting, standing and supine positions on amplitude of accommodation (AA) and near point of convergence (NPC) in myopic individuals. Methods: A cross-sectional study was conducted on 60 optometry undergraduates aged 19–30 years with mild to moderate myopia. Comprehensive eye examinations were performed and AA and NPC were assessed in three postures. AA was measured monocularly using the push-up method with a Royal Air Force ruler and NPC was measured binocularly with a pen torch and 0.30 logMAR (6/12) letters. Each test was repeated thrice per posture and mean values were analyzed using one-way ANOVA. Results: Mean AA in the right eye was 8.48±2.94 D (sitting), 7.89±2.74 D (standing) and 7.38±2.17 D (supine), with no significant difference (p=0.077). NPC averaged 5.38±1.15 cm (sitting), 5.38±1.15 cm (standing) and 5.15±1.45 cm (supine), also not significant (p=0.53). Conclusions: While posture did not significantly influence AA or NPC, a trend toward better accommodative response was seen in the sitting position. These findings indicate that sitting may provide greater visual comfort for myopes during near tasks, highlighting posture’s potential role in visual performance.